Analisis Pemasaran Online Terhadap Peningkatan Penjualan (Studi Kasus @Pabrikkeripikpisang.Id di Bandar Lampung) - Habiburahman; Febriyani, Selvi (Jurnal EMT KITA, 2023)
With technologicaly developments making high use of the internet this day, many of business owners use the internet as a promotial place in their marketing. One of them is a business owner from a banana chip factory(@pabrikkeripikpisang.id) that markets their products through social media Instagram. In this research, author wanted to find out how business owner of the banana chip factory can carry out online marketing and to find whether online marketing affects of using the marketing mix startegy. The method ini this research is used a descriptive qualitative method, in collecting this data in the form of conducting interviews with the owner of the banana chip factory (@pabrikkeripikpisang.id) as well as carrying out documentation by following Instagram @pabrikkeripikpisang.id. The results of this research indicate that instagram is a social media that is easy to used and cost-effective. Using Instagram can make products more famous among the public. In selling via Instagram, the owner admits that Instagram is very infuential in its promotional activities